Hydrogeological Risk Assessment for Groundwater Conservation in the Northeastern Slope Area of Mount Arjuno, Pasuruan Regency, East Java, Indonesia - Sari Bahagiarti Kusumayudha; Puji Pratiknyo; Herry Riswandi; Eni Muryani (Faculty of Geography, Universitas Gadjah Mada, 2021)
The northeastern slope of Mount Arjuno, Pasuruan district, East Java province, Indonesia represents a vast and good groundwater resource quality, generally be exploited by some companies for drinking water industries. Water unbalance and quality degradation is presumed to arise because groundwater extraction volume is getting bigger but less control by the regency authority. This study is to figure out the geologic condition and hydrogeological system, conduct groundwater exploitation risk assessment, and develop a conservation program. The study results show that the study area's geomorphological units can be divided into the volcanic summit, volcanic slope, fluvial plain, and anticlinal hills. The lithology comprises sandstone, breccia, and andesite lava of Mount Arjuno and Mount Welirang. The geological structures are anticline, normal fault, and lateral slip fault. Hydrologically, there are three watersheds, including Lumbangrejo, Ketanireng, and Prigen watersheds. The aquifers comprise unconfined to semi-confined aquifers with fissures and intergranular porosity. Based on risk assessment valuation, Pecalukan village of the Ketanireng watershed and Lumbangrejo village of the Lumbangrejo watershed are categorized as very high groundwater vulnerability zones, Karangrejo and Sukoreno villages of the Lumbangrejo watershed, Kedungringin, Kepulungan, and Gunungsari villages of the Ketanireng watershed are categorized as medium vulnerability zone. While, Ngorong village of the Lumbangrejo watershed, Gempeng, Oro-Ombo, Kalisat, and Dukuhsari villages of the Prigen watershed belong to the low vulnerability zone. The proposed conservation programs involve profitable water use safety campaigns, domestic waste, and industrial wastewater management, agricultural activities controlling, sandstone mining regulation, and reforestation.